Suksesi Kepemimpinan dalam Pemikiran Ibnu Khaldun : Relevansinya dengan Kepemimpinan Era Reformasi di Indonesia - Christy Pransisca; Hery Noer Aly; Ismail Ismail (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This research discusses the concept of leadership succession according to Ibnu Khaldun which focuses on the process of cyclical change of power and is influenced by social solidarity (asabiyah), military strength, leader legitimacy, economic factors, and external influences. Ibn Khaldun emphasized that strong leadership originates from groups with high solidarity, but the weakening of the asabiyah will cause the downfall of the dynasty and trigger succession. This research also examines the relevance of Ibnu Khaldun's theory in the leadership context of the reform era in Indonesia, where political dynamics are influenced by internal and external factors, including political parties, the economy and social inequality. The research was carried out through a descriptive qualitative approach with library research methods, using primary and secondary sources which included the works of Ibnu Khaldun and related literature. Data analysis was carried out using the content analysis method, which aims to understand Ibn Khaldun's views in the context of political and religious sociology. The research results show that Ibn Khaldun's theory of leadership succession provides a relevant perspective in understanding political stability, changes in power, and the challenges faced in maintaining government in the modern era.Keywords: Leadership Succession, Social Inequality, Reformation Era, Leadership Dynamics Abstrak: Penelitian ini membahas konsep suksesi kepemimpinan menurut Ibnu Khaldun yang berfokus pada proses pergantian kekuasaan secara siklis dan dipengaruhi oleh solidaritas sosial (asabiyah), kekuatan militer, legitimasi pemimpin, faktor ekonomi, serta pengaruh eksternal. Ibnu Khaldun menekankan bahwa kepemimpinan yang kuat berawal dari kelompok dengan solidaritas tinggi, namun melemahnya asabiyah akan menyebabkan kejatuhan dinasti dan memicu suksesi. Penelitian ini juga mengkaji relevansi teori Ibnu Khaldun dalam konteks kepemimpinan era reformasi di Indonesia, di mana dinamika politik dipengaruhi oleh faktor internal dan eksternal, termasuk partai politik, ekonomi, dan ketimpangan sosial. Penelitian dilakukan melalui pendekatan kualitatif deskriptif dengan metode riset pustaka (library research), menggunakan sumber primer dan sekunder yang mencakup karya-karya Ibnu Khaldun serta literatur terkait. Analisis data dilakukan dengan metode analisis isi, yang bertujuan untuk memahami pandangan Ibnu Khaldun dalam konteks sosiologi politik dan agama. Hasil penelitian menunjukkan bahwa teori suksesi kepemimpinan Ibnu Khaldun memberikan perspektif yang relevan dalam memahami stabilitas politik, perubahan kekuasaan, dan tantangan yang dihadapi dalam menjaga pemerintahan di era modern.Kata kunci: Suksesi Kepemimpinan, Ketimpangan Sosial, Era Reformasi, Dinamika Kepemimpinan